2021
DOI: 10.1038/s41598-021-02720-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium oscillations in the phenotype selection in endothelial cells

Abstract: Angiogenesis is an important process in the formation and maintenance of tissues which is driven by a complex system of intracellular and intercellular signaling mechanisms. Endothelial cells taking part in early angiogenesis must select their phenotype as either a tip cells (leading, migratory) or a stalk cells (following). Recent experiments have demonstrated that rapid calcium oscillations within active cells characterize this phenotype selection process and that these oscillations play a necessary role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Additionally, ECs under hypoxia act differently from ECs under hypoxia serum starvation (representing PAD conditions), which is a future aspect to be investigated with our modeling strategy. Previous works discuss the role of calcium oscillations on endothelial cell patterning ( Debir et al, 2021 ). In this work, we consider the signaling through calcium in the endoplasmic reticulum and cytoplasm, with the extracellular calcium effect accounted for through CRAC channels calcium influx and the Ca++–Na + exchanger (under hypoxia).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ECs under hypoxia act differently from ECs under hypoxia serum starvation (representing PAD conditions), which is a future aspect to be investigated with our modeling strategy. Previous works discuss the role of calcium oscillations on endothelial cell patterning ( Debir et al, 2021 ). In this work, we consider the signaling through calcium in the endoplasmic reticulum and cytoplasm, with the extracellular calcium effect accounted for through CRAC channels calcium influx and the Ca++–Na + exchanger (under hypoxia).…”
Section: Discussionmentioning
confidence: 99%
“…The ERK signaling pathway, in turn, was crucial to induce the expression of several tip cell markers, including DLL4 and flt4, to promote filopodia formation and to stimulate endothelial cell migration [129]. Computational modeling confirmed that higher InsP 3 -dependent Ca 2+ spiking is associated with tip cell phenotype selection and favors Dll4 expression [195]. Future studies will have to evaluate this mechanism in mammalian capillaries, which represent the main source of neovessels after an ischemic event or during tumor growth.…”
Section: Vegf-induced Intracellular Ca 2+ Oscillations Select Endothe...mentioning
confidence: 94%
“…To sustain endothelial homeostasis and execute needed functions, ECs depend to varying degrees on changes in intracellular free Ca 2+ concentration ([Ca 2+ ] i ) (9). Calcium is a ubiquitous second messenger that is tightly regulated inside the cell by Ca 2+ ion channels and receptors (10,11).…”
Section: Introductionmentioning
confidence: 99%